Human Development's Impact on Economic Welfare in West Sumatra : An Analysis of Education, Health, and Employment Factors (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the determinants of economic welfare in West Sumatra Province, focusing on the role of Human Development Index (HDI) components, namely Life Expectancy (LE), Expected Years of Schooling (EYS), Mean Years of Schooling (MYS), and Per Capita Expenditure (PCE). The analysis covers the period from 2017 to 2023 across 19 districts and cities, employing a quantitative approach with panel data regression using the Fixed Effect Model (FEM). Economic welfare is proxied by Gross Regional Domestic Product (GRDP) per capita, which is widely recognized as a reliable measure of regional prosperity. The findings reveal that although LE, EYS, and MYS show positive coefficients, their impact on economic welfare is statistically insignificant, suggesting that improvements in health and education require a longer time horizon to translate into measurable economic outcomes. In contrast, PCE demonstrates a strong and significant positive effect, indicating its critical role as a driving factor of regional welfare disparities. This outcome suggests that improvements in household consumption capacity directly enhance economic well-being more substantially than non-monetary HDI indicators within the studied context. The results highlight the importance of prioritizing income growth and expenditure-based interventions while maintaining long-term investment in health and education sectors to ensure inclusive and sustainable welfare. From a policy perspective, the government should strengthen programs that expand household purchasing power, while integrating them with education and healthcare development to achieve balanced and sustainable progress. This research contributes to the empirical literature by providing region-specific evidence on the interplay between HDI components and economic welfare, emphasizing the dominance of economic variables over social indicators in short- to medium-term welfare outcomes, and offering insights for future development strategies.